2011
DOI: 10.1038/aps.2011.67
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-17A is involved in development of spontaneous pulmonary emphysema caused by Toll-like receptor 4 mutation

Abstract: Aim: To explore the pathogenic role of Th17 cells and interleukin-17A (IL-17A)-associated signaling pathways in spontaneous pulmonary emphysema induced by a Toll-like receptor 4 mutant (TLR4 mut ). Methods: Lungs were obtained from wild-type (WT) or TLR4 mut mice that were treated with or without recombinant mouse IL-17A (1 μg·kg, ip) from the age of 3 weeks to 3 months. Pulmonary emphysema was determined using histology, immunochemistry, and biochemical analysis. T cell polarization was determined with flow c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…oxidative stress, apoptosis) implicated in emphysema. For example, while IL‐17A can protect against oxidative stress‐associated emphysematous changes in TLR4‐deficient mice, IL‐17A appears to directly promote CS‐induced alveolar cell apoptosis in wild‐type mice . Regarding the latter, at least in the context of IL‐6‐induced alveolar cell apoptosis that is the primary pathological emphysematous process in gp130 F/F mice, our data presented here suggest that IL‐17A does not promote IL‐6‐induced cellular apoptosis.…”
Section: Discussionmentioning
confidence: 57%
“…oxidative stress, apoptosis) implicated in emphysema. For example, while IL‐17A can protect against oxidative stress‐associated emphysematous changes in TLR4‐deficient mice, IL‐17A appears to directly promote CS‐induced alveolar cell apoptosis in wild‐type mice . Regarding the latter, at least in the context of IL‐6‐induced alveolar cell apoptosis that is the primary pathological emphysematous process in gp130 F/F mice, our data presented here suggest that IL‐17A does not promote IL‐6‐induced cellular apoptosis.…”
Section: Discussionmentioning
confidence: 57%
“…IL-23-dependent Th17 cells can invade the target organ and promote the development of organ-specific autoimmune inflammation [41,42] . The current study demonstrated that DZ2002 treatment markedly reduced the Th17 population in NZB/W F 1 mice, accompanied by a comprehensive suppression of IL-17 production.…”
Section: Discussionmentioning
confidence: 99%
“…However, whether there is an association of Th17 cells or IL-17 cytokines with TLR4 in EAN remains poorly documented. Wang et al [18] found that IL-17A participated in development of spontaneous pulmonary emphysema which was caused by Toll-like receptor 4 mutation.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al . [ 18 ] found that IL-17A participated in development of spontaneous pulmonary emphysema which was caused by Toll-like receptor 4 mutation.…”
Section: Introductionmentioning
confidence: 99%